2011
DOI: 10.1177/1757975910393168
|View full text |Cite
|
Sign up to set email alerts
|

Movement as Investment for Health

Abstract: Movement as Investment for Health (Bewegung als Investition in Gesundheit or BIG) was a multidimensional research study in participatory physical activity promotion among socially disadvantaged women in a deprived neighbourhood in Erlangen, Germany. It aimed at making full use of health-promoting effects of movement and developing integrated evaluation through approaches from different disciplines. We defined the target population through national health survey data, and determined important intervention and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 4 publications
0
11
0
3
Order By: Relevance
“…Ces comités peuvent prendre des formes diverses avec des représentants des différentes parties prenantes, et notamment des membres des communautés pour lesquelles les programmes ont été créés. Frahsa et al (16), par exemple, décrit un comité de ce genre en Allemagne dans lequel on a donné aux femmes issues de communautés minoritaires une voix dans la conduite de l'évaluation de la mise en oeuvre de l'intervention. Une autre forme de médiation a lieu au travers du plaidoyer, comme l'illustrent les cas décrits par Sleet et al…”
Section: L'utilisation Des Données Probantesunclassified
“…Ces comités peuvent prendre des formes diverses avec des représentants des différentes parties prenantes, et notamment des membres des communautés pour lesquelles les programmes ont été créés. Frahsa et al (16), par exemple, décrit un comité de ce genre en Allemagne dans lequel on a donné aux femmes issues de communautés minoritaires une voix dans la conduite de l'évaluation de la mise en oeuvre de l'intervention. Une autre forme de médiation a lieu au travers du plaidoyer, comme l'illustrent les cas décrits par Sleet et al…”
Section: L'utilisation Des Données Probantesunclassified
“…The linear model of knowledge transfer has been challenged [ 41 ], and the involvement of stakeholders in framing problems has also been recognized [ 48 , 51 53 ]. In addition to the need to increase more participative approaches with collaboration, the production of knowledge for policymaking includes attributes such as the interdisciplinary approach, links between theory and practice, participatory approaches employing different knowledge forms and including a reflection on the variety of knowledge elements [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses of BIG have demonstrated that its exercise classes do indeed reach women in difficult life situations (32). There is also evidence of the health-promoting effects of BIG on women.…”
Section: Big-reach Of Exercise Programs Attendance and (Health) Effmentioning
confidence: 98%
“…There is also evidence of the health-promoting effects of BIG on women. Women attending BIG exercise classes reported increased social networks and beneficial effects on their physical and mental well-being (29,32). By taking part in the cooperative planning process, the women reported increased self-efficacy, as they were empowered to voice their interests and increase their knowledge of political and administrative processes (29).…”
Section: Big-reach Of Exercise Programs Attendance and (Health) Effmentioning
confidence: 99%